Community Assembly and Co-occurrence Patterns Underlying the Core and Satellite Bacterial Sub-communities in the Tibetan Lakes - Yan, Qi; Deng, Jianming; Wang, Feng; Liu, Yongqin; Liu, Keshao (Frontiers in Microbiology, 2021)
Microbial communities normally comprise a few core species and large numbers of satellite species. These two sub-communities have different ecological and functional roles in natural environments, but knowledge on the assembly processes and co-occurrence patterns of thecore and satellite species in Tibetan lakes is still sparse. Here, we investigated the ecological processes and co-occurrence relationships of the core and satellite bacterial sub-communities in the Tibetan lakes via 454 sequencing of 16S rRNA gene. Our studies indicated that the core and satellite bacterial sub-communities have similar dominated taxa (Proteobacteria, Bacteroidetes and Actinobacteria). But the core sub-communities were less diverse, and exhibited a stronger distance-decay relationship than the satellite sub-communities. In addition, node-level topological revealed the core sub-communities had more complex co-occurrence associations, and were primarily driven by stochastic processes (57.91%). By contrast, the satellite sub-communities were mainly governed by deterministic processes (75.85%). Overall, this study demonstrated the differences in the core and satellite sub-community assemblies and stabilities, suggesting the importance of considering species traits to understand the biogeographic distribution of bacterial communities in high-altitude lakes.